Strategies and Tools that Stimulate Creative Thinking in Museum Practice - Carvalho, Ana (2020)
Creative thinking is likely to be one of the essential skills for the 21st Century, not just for museum professionals but also for professionals across all areas of our society. As society changes, an array of new technologies and practices emerge, which require flexibility and improvisation from museums and museum professionals. Creative thinking is one of the skills that are crucial to adapt and respond more effectively to changing realities, whether in digital or non-digital environments. This learning object outlines several strategies and tools that stimulate creative thinking in museum practice. It presents five strategies, focusing on the value of lifelong learning, divergent and convergent thinking, remixing and combining ideas, and the role of constraints and failure in the creative process. It introduces four tools that can be applied in daily museum practice: observation, mind mapping, documenting creative practice and SCAMPER. This learning object is part of the module “Creative Thinking Skills” of the MOOC “Essential Digital Skills for Museum Professionals” developed by Project Mu.SA – Museum Sector Alliance (575907-EEP-1-2016-1-EL-EPPKA2-SSA).